The Herding Phenomenon in The Indonesian Stock Market: An Analysis of CSSD & CSAD and its Implications for Investors and Regulators - Wibowo, Alfi Hikami; Kunawangsih, Tri; S, Mona Adriana (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to identify the presence of herding behavior in the Indonesian stock market throughout 2024, using the LQ45 Index as a market proxy. The analysis employs the Cross-Sectional Standard Deviation (CSSD) and Cross-Sectional Absolute Deviation (CSAD) models to measure the dispersion of stock returns under normal and extreme market conditions. The findings reveal no statistically significant evidence of herding behavior, although weak indications are observed during extreme negative market conditions. These results support the notion of a relatively efficient market, aligning with the Efficient Market Hypothesis (EMH). The CSSD and CSAD models are found to be complementary in analyzing investor behavior.